Effects of information access cost, confidence judgment and overconfidence bias on information retrieval strategy and task performance. (September 2014) - Yang, Jessie X.; Park, Taezoon; Wickens, Christopher D.; Helander, Martin G.
Information access cost has been reported to be one determinant of one's information retrieval strategy. However, the "expected gain" of an information retrieval strategy has not received much attention. The present study aimed to examine the effects of confidence judgment and overconfidence bias, besides the information access cost, on the choice of information retrieval strategy and task performance. The results showed that both information access cost and confidence judgment of memory accuracy affected information access attempts, and overconfidence bias harmed information retrieval performance.